The effect of intraday periodicity on realized volatility measures - Holger Dette; Vasyl Golosnoy; Janosch Kellermann (Metrika, 2022)
We focus on estimating daily integrated volatility ( IV ) by realized measures based on intraday returns following a discrete-time stochastic model with a pronounced intraday periodicity (IP). We demonstrate that neglecting the IP-impact on realized estimators may lead to invalid statistical inference concerning IV for a common finite number of intraday returns. For a given IP functional form, we analytically derive robust IP-correction factors for realized measures of IV as well as their asymptotic distributions. We show both in Monte Carlo simulations and empirically that the proposed bias corrections are the robust way to account for IP by computing realized estimators.
Keywords: 510; Bipower variation; Integrated volatility; Integrated quarticity; Intraday periodicity